ANALISIS PARTISIPASI ANGGOTA YANG AKTIF PADA UNIT TOKO KOPERASI PEGAWAI NEGERI UNIVERSITAS TANJUNGPURA PONTIANAK - Imj, Rosilia; Parijo, Parijo; BU, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe research started from the researcher interest on the buying and selling activities at KPN Untan less developed shop units and the number of members who actively participate in the meaning of shopping for basic needs is relatively small compared to the number of members registered in KPN Untan. Whereas at the beginning of the establishment of the unit store KPN Untan was a fairly developed shop units. The general problem in this research was "how active members participate in the unit of civil service cooperative shop". This research aimed to provide an overview of the participation of active members shop cooperatives unit. The method used in this research was descriptive method. The results showed that active participation of many members in shopping for secondary needs not on tertiary needs, then the average motivation of KPN Untan members in shopping of the store unit amounted to 41.18% but did not encourage them to continue to participate optimally, giving credit to members in shopping for basic needs expressed by members of 64.71%, shopping procedures set by the board and felt easily stated by members of 58.82%. Overall the percentage was in enough category. Keywords: Analysis, ActiveMembers Participation, Unit Store KPN Untan